Biomass burning and fungal spores as sources of fine aerosols in Yangtze River Delta, China – Using multiple organic tracers to understand variability, correlations and origins. (August 2019) - Xu, Jingsha; Jia, Chunrong; He, Jun; Xu, Honghui; Tang, Yu-Ting; Ji, Dongsheng; Yu, Huan; Xiao, Hang; Wang, Chengjun
Abstract: Research is restricted regarding impacts of biomass burning (BB) on fine aerosol (PM2.5 ), due mainly to lack of specific BB tracers. This study aims to characterize the variability, distributions, and contributions of BB and fungal spores as sources of PM2.5 using a multiple organic tracer approach. PM2.5 samples were collected at four representative sites in Yangtze River Delta (YRD), China every 6 days for one year. In the laboratory, samples were analyzed for three anhydrides (levoglucosan, mannosan, and galactosan), two sugar alcohols (arabitol and mannitol), water-soluble inorganic ions, and elemental/organic carbon (EC/OC). Levoglucosan was the most abundant BB tracer (mean concentration = 81 ng/m 3 ), and fungal spore tracers arabitol and mannitol had similar abundances (5.6 and 5.7 ng/m 3, respectively). Anhydrides and sugar alcohols had high within-group correlations, indicating their respective common sources. Concentrations of tracers displayed large temporal variations but small spatial variations, suggesting strong seasonality in BB and fungal spore sources. BB sources were burning of grass, pine needles, hardwood and crop straw, which were originated from transboundary/cross-region transport and local fire spots. PCA analyses revealed that the common sources of fine aerosols in YRD were secondary inorganic aerosols, soil dust, BB and fungal spores. Graphical abstract: Image 1 Highlights: Multiple organic tracers were measured for biomass burning (BB) and fungal spores. Tracers displayed large temporal variations but small spatial variations. BB tracers peaked in winter, and fungal spore tracers peaked in summer. BB types were burning of pine needles, hardwood, softwood, and crop straws. BB accounted for 43% of total variance in PCA analysis on an annual basis. Abstract : BB and fungal spore tracers exhibited strong seasonality and day-to-day variation, respectively; while their spatial variation was small, indicating larger contributions from regional sources.